DEVELOPMENT OF KICKBOXING WAKO AS AN OLYMPIC SPORTS IN UKRAINE - Orel, I. O.; Hamma, T. V.; Hirak, A. M.; Nohas, A. O.; Hutsman, S. V. (Rehabilitation and Recreation, 2021)
In Ukraine and the world, kickboxing occupies a special place as one of the brightest sports, which is developing rapidly and already has Olympic status. The article considers what WAKO kickboxing is, its origin and development in Ukraine since Soviet times and until now. The participation of Ukrainian athletes in both international and regional arenas is analyzed. The main problems of kickboxing development are highlighted. It has been proved that with its achievements the Kickboxing Federation of Ukraine WAKO leads a characteristic direction to the recognition of this sport as Olympic, and in a very short time non-Olympic kickboxing was formed as a world leader in martial arts. Sport always motivates a person to achieve certain goals. Kickboxing is a unique martial art that harmoniously combines elements of karate, boxing and Thai boxing. Practicing this sport helps to educate the character, maintain good physical shape and health, and gives a person an effective means of self-defense. It is recognized that WAKO is multifaceted and interesting, and most importantly – it is an Olympic sport with rich functionality and a fairly short but high-profile history. Despite the global problems of today, competitiveness, this sport is interesting, diverse, spectacular. Thanks to the persistence of athletes, the support of the authorities, the coordinated work of the presidium and the coaching staff, Ukraine is one of the ten strongest teams in the world. For ten years, the sport was closely monitored by the IOC to participate in the most prestigious competition of four years – the Olympic Games.